Business Meets the Humanities: The Human Perspective in University-Industry Collaboration - Martina Skrubbeltrang Mahnke; Mikka Nielsen; Matilde Lykkebo Petersen; Lise Tjørring (Routledge, 2023)
Within the last decades, universities are increasingly expected and measured by their direct engagement in collaborations beyond academia. Exploring the potential that lies in university-business collaborations, the present anthology attends to the dilemmas, dualities, and challenges that follow such collaborations, especially in the academic traditions of the social sciences and humanities. Each contribution investigates how the human perspective – a perspective that highlights how complex knowledge and a deep understanding of human everyday life – enriches companies' processes, products, services, and ideas. Some chapters focus on collaborations between researchers and business practitioners, others focus on teaching examples involving students in the collaborative work with businesses and organisations, and again others contribute with more theoretical considerations. By gathering hands-on experiences, the book provides readers with inspirations, reflections on, and insights into university-business collaborations. This book, therefore, is intended for researchers within the humanities and social sciences, who want to get a deeper understanding of the practice of such collaborations.
Keywords: 650; business; design research; human; human-centred architecture; management; Open-innovation; organization; society; university